1981
DOI: 10.1001/jama.1981.03320060037018
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Fetus With a Urinary Tract Malformation

Abstract: Obstetric sonography revealed urinary tract malformations in 13 fetuses. Six had severe dysplastic lesions incompatible with postnatal life; in all six, oligohydramnios and inability to detect normal kidney or bladder allowed appropriate counseling and management. Four fetuses had unilateral lesions (three hydronephrotic, one multicystic); all had evidence of adequate contralateral function and were successfully treated after delivery near term. Three fetuses had bilateral hydronephrosis secondary to urethral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…In fact high urinary obstructions are usually detectable ultrasonically in the second trimester, but are mainly noted in the third trimester of pregnancy. Sometimes clinical pictures such as the variation of amniotic fluid are the first signs of urinary malformation [5,9]. In our experience, oligohydramnios was always associated with a very poor fetal prognosis; on the other hand, polyhydramnios was frequently associated with upper urinary tract obstruction without correlation to fetal prognosis.…”
Section: Commentsupporting
confidence: 44%
See 1 more Smart Citation
“…In fact high urinary obstructions are usually detectable ultrasonically in the second trimester, but are mainly noted in the third trimester of pregnancy. Sometimes clinical pictures such as the variation of amniotic fluid are the first signs of urinary malformation [5,9]. In our experience, oligohydramnios was always associated with a very poor fetal prognosis; on the other hand, polyhydramnios was frequently associated with upper urinary tract obstruction without correlation to fetal prognosis.…”
Section: Commentsupporting
confidence: 44%
“…In our experience, oligohydramnios was always associated with a very poor fetal prognosis; on the other hand, polyhydramnios was frequently associated with upper urinary tract obstruction without correlation to fetal prognosis. In the perinatal management of congenital urinary malformation, not only should the character of the amniotic fluid be taken into account, but also the gestational age, the status of fetal development, the L/S amniotic fluid ratio and the potential for intrauterine therapy [4][5][6][7][8][9]. Taking into consideration the gestational age and genetic counselling, the chromosomic analysis of the amniotic fluid is very useful; the association between renal ectopia, hydronephrosis, polycystic kidney and trisomy of chromosomes 9 and 18 is very frequent.…”
Section: Commentmentioning
confidence: 99%
“…Harrison and coworkers [1][2][3] and other investigators 4,5 have established that the fetus with an obstructed urinary tract may benefit from prenatal decompression. The difficulty arises in identifying which fetuses have obstruction and which fetuses with urinary tract obstruction will truly benefit from decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison's group was able to demonstrate that early obstruction resulted in more histological renal damage than obstruction 3 Carr et al have shown, that mid-gestation is the period of greatest renal growth and development. 4 They suggest, that significant obstruction and hydronephrosis in early mid-gestation would have its greatest impact on renal development.…”
Section: Pathophysiologymentioning
confidence: 99%